Room‐temperature dislocation plasticity in SrTiO3 tuned by defect chemistry. Issue 2 (6th October 2021) - Stich, Stephan; Ding, Kuan; Muhammad, Qaisar Khushi; Porz, Lukas; Minnert, Christian; Rheinheimer, Wolfgang; Durst, Karsten; Rödel, Jürgen; Frömling, Till; Fang, Xufei
Abstract: Dislocations have been identified to modify both the functional and mechanical properties of some ceramic materials. Succinct control of dislocation‐based plasticity in ceramics will also demand knowledge about dislocation interaction with point defects. Here, we propose an experimental approach to modulate the dislocation‐based plasticity in single‐crystal SrTiO3 based on the concept of defect chemistry engineering, for example, by increasing the oxygen vacancy concentration via reduction treatment. With nanoindentation and bulk compression tests, we find that the dislocation‐governed plasticity is significantly modified at the nano‐/microscale, compared to the bulk scale. The increase in oxygen vacancy concentration after reduction treatment was assessed by impedance spectroscopy and is found to favor dislocation nucleation but impede dislocation motion as rationalized by the nanoindentation pop‐in and nanoindentation creep tests.